A matte pet composite film and a method for preparing the same
Patent Information
- Application Number
- CN202611306573.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-23
AI Technical Summary
[0002]磨砂PET复合膜,是一种以聚对苯二甲酸乙二醇酯(PET)为基材的表面功能化薄膜,通过对PET薄膜表面进行磨砂处理,改变薄膜表面的微观形态,从而获得均匀、细腻的哑光效果,此外,表面磨砂在一定程度上能赋予PET薄膜额外的功能,然而,在实际应用过程中,磨砂PET复合膜也暴露出一些固有的不足与挑战,首先是层间粘结力问题,磨砂层通常采用涂布含有消光粒子的涂层或采用物理压绞等方式实现,若涂层配方设计不合理、消光粒子与树脂基体相容性差,极易导致磨砂层本身的内聚强度不足或与基体的附着力薄弱,在使用中出现涂层粉化、脱落等现象;其次,由于磨砂层表面存在微观凹凸结构,其机械强度通常低于光滑表面,更容易被硬物刮伤,同时这种微观结构也使得磨砂表面比光滑表面更易藏污纳垢,湿水时水滴相较光滑表面更不易滑落,长此以往,容易影响PET复合膜的实用性和耐久性,因此,磨砂PET复合膜技术仍有待进一步改进
(1)本发明在磨砂PET复合膜添加了特定的高分子树脂,所述高分子树脂由氟硅改性聚氨酯丙烯酸酯、丙烯酸聚硅氧烷、丙烯酸(酯)类/硬脂醇丙烯酸酯/聚二甲基硅氧烷甲基丙烯酸酯共聚物混合得到。其中,氟硅改性聚氨酯丙烯酸酯作为主体骨架,其聚氨酯链段提供优异的韧性和附着力基础,同时分子中引入的氟碳链段具有较低的表面能,能显著增强涂层的疏水疏油特性;丙烯酸聚硅氧烷的长链硅氧烷结构提供深度柔顺性,有效缓冲固化收缩应力,防止涂层因内应力过大而从基材剥离,其硅氧烷链段亦贡献低表面能;丙烯酸(酯)类/硬脂醇丙烯酸酯/聚二甲基硅氧烷甲基丙烯酸酯共聚物中的聚二甲基硅氧烷链段在固化过程中更易向涂层-空气界面迁移并富集,与氟硅改性聚氨酯丙烯酸酯中的氟碳链段、丙烯酸聚硅氧烷及有机-无机磨料表面的十二烷基硅烷疏水层协同作用,在涂层表面构建出均匀、致密且具有极低表面能的保护层,极大减弱了水、油等常见污渍与涂层表面的范德华力附着力,使污染物难以润湿和附着。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane material technology and relates to a frosted PET composite film and its preparation method. Background Technology
[0002] Frosted PET composite film is a surface-functionalized film based on polyethylene terephthalate (PET). By frosting the surface of the PET film, its microstructure is altered, resulting in a uniform and delicate matte finish. Furthermore, surface frosting can impart additional functionality to the PET film. However, in practical applications, frosted PET composite film also reveals some inherent shortcomings and challenges. The first is the issue of interlayer adhesion. The frosted layer is typically achieved by coating with matte particles or through physical bonding. If the coating formulation is... Unreasonable design and poor compatibility between matte particles and the resin matrix can easily lead to insufficient cohesive strength of the frosted layer itself or weak adhesion to the matrix, resulting in phenomena such as coating powdering and peeling during use. Secondly, due to the micro-uneven structure on the surface of the frosted layer, its mechanical strength is usually lower than that of a smooth surface, making it easier to be scratched by hard objects. At the same time, this micro-structure also makes the frosted surface more prone to accumulating dirt and grime than a smooth surface, and water droplets are less likely to slide off when wet. Over time, this can easily affect the practicality and durability of the PET composite film. Therefore, the frosted PET composite film technology still needs further improvement. Summary of the Invention
[0003] The purpose of this invention is to provide a frosted PET composite film and its preparation method. This invention provides a frosted PET composite film by introducing a polymer resin obtained by compounding three resins and an organic-inorganic abrasive grafted with hydrophobic segments into the frosted layer. This not only endows the composite film with good wear resistance, but also makes the composite film exhibit good adhesion, water contact angle and oil contact angle, thereby achieving long-lasting and efficient water and stain resistance.
[0004] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a frosted PET composite film, the frosted PET composite film comprising a PET base film and a frosted layer, wherein the raw materials of the frosted layer include a polymer resin, organic-inorganic abrasives, leveling agents, photoinitiators, ultraviolet absorbers, defoamers, and diluents, and the polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer; Preferably, the weight ratio of the fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer is 4.5-5.5:2.5-3.5:1.5-2.5.
[0005] Preferably, the weight ratio of the polymer resin, organic-organic abrasive, leveling agent, photoinitiator, ultraviolet absorber, defoamer, and diluent is 30-34:15-25:0.6-0.7:4.8-5.2:0.12-0.18:0.25-0.35:40-45.
[0006] Specifically, the preparation of the organic-inorganic abrasive includes the following steps: A1. Mix nano-silica and N,N-dimethylformamide, disperse evenly, then add γ-glycidyl etheroxypropyltrimethoxysilane and dodecylmethyldiethoxysilane. Adjust the pH to 4-5 by adding acetic acid solution dropwise. Stir at 60-80℃ for 6-8 hours, centrifuge at 2000 rpm for 10 minutes, discard the supernatant, wash, and vacuum dry to obtain organic-inorganic abrasive.
[0007] Preferably, the average particle size of the nano-silica in step A1 is 5-20 nm; the weight ratio of the nano-silica, N,N-dimethylformamide, γ-glycidyl etheroxypropyltrimethoxysilane, and dodecylmethyldiethoxysilane is 1:15-25:0.1-0.3:0.15-0.4.
[0008] Secondly, the present invention provides a method for preparing the frosted PET composite film described in the first aspect, wherein the method for preparing the frosted PET composite film specifically includes the following steps: B1. Mix the polymer resin, leveling agent, defoamer, and 1 / 2 of the diluent evenly. Add the organic-inorganic abrasive and pre-disperse at 800 rpm for 8-12 minutes. Then add the photoinitiator, ultraviolet absorber, and the remaining diluent and stir at 1000 rpm for 20-30 minutes to obtain the frosted functional layer coating. B2. The frosted functional layer coating is evenly applied to the surface of the PET film, dried under hot air at 60-80℃, and then placed in a UV curing oven for UV curing. After cooling to room temperature, the film is rolled up and cured at room temperature and 50% relative humidity for 24-28 hours to obtain the frosted PET composite film.
[0009] Preferably, the coating amount in step B2 is 8-20 g / m². 2 The UV curing radiation dose is 400-800 mJ / cm². 2 The time is 1-3 seconds.
[0010] The beneficial effects of this invention are: (1) The present invention adds a specific polymer resin to the frosted PET composite film, wherein the polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer. Among them, fluorosilicone modified polyurethane acrylate serves as the main framework, with its polyurethane segments providing excellent toughness and adhesion. At the same time, the fluorocarbon segments introduced into the molecule have low surface energy, which can significantly enhance the hydrophobic and oleophobic properties of the coating. The long-chain siloxane structure of acrylic polysiloxane provides deep flexibility, effectively buffering curing shrinkage stress and preventing the coating from peeling off from the substrate due to excessive internal stress. Its siloxane segments also contribute low surface energy. The polydimethylsiloxane segments in the acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer are more likely to migrate and accumulate to the coating-air interface during the curing process. They work synergistically with the fluorocarbon segments in the fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and the dodecylsilane hydrophobic layer on the surface of the organic-inorganic abrasive to build a uniform, dense protective layer with extremely low surface energy on the coating surface. This greatly reduces the van der Waals adhesion of common stains such as water and oil to the coating surface, making it difficult for contaminants to wet and adhere.
[0011] (2) The present invention uses a one-time mixed silane coupling method to prepare organic-inorganic abrasives. The epoxy group of γ-glycidoxypropyltrimethoxysilane can provide active sites for subsequent chemical cross-linking with the polymer resin matrix. The long chain structure of dodecylmethyldiethoxysilane helps to form a low surface energy monomolecular hydrophobic outer layer. In addition, the epoxy active groups on the surface of the abrasive can undergo ring-opening reaction with the active groups (such as hydroxyl, urethane bonds, etc.) of the fluorosilicone modified polyurethane acrylate, acrylic polysiloxane and other resins in the formulation during the UV curing process to form strong covalent bonds "chemical rivets", which greatly enhances the interfacial bonding force between the abrasive and the resin matrix, and together endow the abrasive layer with excellent hydrophobicity and anti-fouling properties.
[0012] (3) The present invention provides a frosted PET composite film, which introduces a polymer resin obtained by compounding three resins and an organic-inorganic abrasive grafted with hydrophobic segments into the frosted layer, so that the surface of the composite film exhibits good water contact angle and oil contact angle, thereby achieving long-lasting and efficient water and dirt resistance. Detailed Implementation
[0013] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0014] Unless otherwise specified, all other materials, reagents, etc. used in all embodiments and comparative examples of this invention are commercially available.
[0015] The preparation method of the frosted PET composite film described in all embodiments and comparative examples of the present invention includes the following steps: B1. Mix the polymer resin, leveling agent (BYK301), defoamer (BYK1640), and 1 / 2 volume of diluent (trimethylolpropane triacrylate, CAS No. 15625-89-5) evenly. Add the organic-inorganic abrasive and pre-disperse at 800 rpm for 8-12 minutes. Then add the photoinitiator (photoinitiator 184), ultraviolet absorber (Tinuvin 405), and the remaining diluent (trimethylolpropane triacrylate, CAS No. 15625-89-5). Stir at 1000 rpm for 20-30 minutes to obtain the frosted functional layer coating. B2. Apply the frosted functional layer coating evenly to the surface of the PET film, with a coating amount of 10g / m². 2, After drying in hot air at 70℃, it is placed in a UV curing oven at 600mJ / cm². 2 Cured for 2 seconds under a certain radiation dose, cooled to room temperature, wound up, and aged for 26 hours at room temperature and 50% relative humidity to obtain a frosted PET composite film.
[0016] Example 1 A frosted PET composite film, wherein the polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate (Dongguan Jingshang New Material Development Co., Ltd., model UV-9843-9), acrylic polysiloxane (Hubei Xinyuhong Biomedical Technology Co., Ltd., product name acrylic polysiloxane resin), and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer (Shin-Etsu KP-561P, product name silicone acrylate) in a weight ratio of 5:3:2; The weight ratio of the polymer resin, organic-organic abrasive, leveling agent, photoinitiator, ultraviolet absorber, defoamer, and diluent is 32:20:0.65:5:0.15:0.3:42.5. The preparation of the organic-inorganic abrasive includes the following steps: A1. Mix nano-silica and N,N-dimethylformamide, disperse evenly, then add γ-glycidyl etheroxypropyltrimethoxysilane and dodecylmethyldiethoxysilane, adjust the pH to 4.5 by adding acetic acid solution dropwise, stir at 70℃ for 7h, centrifuge at 2000rpm for 10min, discard the supernatant, wash, and vacuum dry to obtain organic-inorganic abrasive; The average particle size of the nano-silica (Nangong Xingjiu New Material Technology Co., Ltd., CAS No. 7631-86-9) mentioned in step A1 is 10 nm; the weight ratio of nano-silica, N,N-dimethylformamide, γ-glycidyl etheroxypropyltrimethoxysilane (Chengfeng, CAS No. 2530-83-8), and dodecylmethyldiethoxysilane (Chengfeng, CAS No. 60317-40-0) is 1:20:0.2:0.28.
[0017] Example 2 A frosted PET composite film, wherein the polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate (Dongguan Jingshang New Material Development Co., Ltd., model UV-9843-9), acrylic polysiloxane (Hubei Xinyuhong Biomedical Technology Co., Ltd., product name acrylic polysiloxane resin), and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer (Shin-Etsu KP-561P, product name silicone acrylate) in a weight ratio of 4.5:2.5:1.5; The weight ratio of the polymer resin, organic-organic abrasive, leveling agent, photoinitiator, ultraviolet absorber, defoamer, and diluent is 30:15:0.6:4.8:0.12:0.25:40; The preparation of the organic-inorganic abrasive includes the following steps: A1. Mix nano-silica and N,N-dimethylformamide, disperse evenly, then add γ-glycidyl etheroxypropyltrimethoxysilane and dodecylmethyldiethoxysilane, adjust the pH to 4 by adding acetic acid solution dropwise, stir at 60℃ for 8h, centrifuge at 2000rpm for 10min, discard the supernatant, wash, and vacuum dry to obtain organic-inorganic abrasive. The average particle size of the nano-silica (Nangong Xingjiu New Material Technology Co., Ltd., CAS No. 7631-86-9) mentioned in step A1 is 5 nm; the weight ratio of nano-silica, N,N-dimethylformamide, γ-glycidyl etheroxypropyltrimethoxysilane (Chengfeng, CAS No. 2530-83-8), and dodecylmethyldiethoxysilane (Chengfeng, CAS No. 60317-40-0) is 1:15:0.1:0.15.
[0018] Example 3 A frosted PET composite film, wherein the polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate (Dongguan Jingshang New Material Development Co., Ltd., model UV-9843-9), acrylic polysiloxane (Hubei Xinyuhong Biomedical Technology Co., Ltd., product name acrylic polysiloxane resin), and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer (Shin-Etsu KP-561P, product name silicone acrylate) in a weight ratio of 5.5:3.5:2.5; The weight ratio of the polymer resin, organic-organic abrasive, leveling agent, photoinitiator, ultraviolet absorber, defoamer, and diluent is 34:25:0.7:5.2:0.18:0.35:45. The preparation of the organic-inorganic abrasive includes the following steps: A1. Mix nano-silica and N,N-dimethylformamide, disperse evenly, then add γ-glycidyl etheroxypropyltrimethoxysilane and dodecylmethyldiethoxysilane, adjust the pH to 5 by adding acetic acid solution dropwise, stir at 80℃ for 6 h, centrifuge at 2000 rpm for 10 min, discard the supernatant, wash, and vacuum dry to obtain organic-inorganic abrasive. The average particle size of the nano-silica (Nangong Xingjiu New Material Technology Co., Ltd., CAS No. 7631-86-9) mentioned in step A1 is 20nm; the weight ratio of nano-silica, N,N-dimethylformamide, γ-glycidyl etheroxypropyltrimethoxysilane (Chengfeng, CAS No. 2530-83-8), and dodecylmethyldiethoxysilane (Chengfeng, CAS No. 60317-40-0) is 1:25:0.3:0.4.
[0019] Comparative Example 1 Compared with Example 1, the only difference is that the fluorosilicone modified polyurethane acrylate in the polymer resin was omitted in Comparative Example 1, and the missing amount was made up by acrylic polysiloxane, acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer with a weight ratio of 3:2. Other conditions were the same as in Example 1.
[0020] Comparative Example 2 Compared with Example 1, the only difference is that the acrylic polysiloxane in the polymer resin was omitted in Comparative Example 2, and the missing amount was made up by fluorosilicone modified polyurethane acrylate and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer in a weight ratio of 5:2. Other conditions were the same as in Example 1.
[0021] Comparative Example 3 Compared with Example 1, the only difference is that the acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer in the polymer resin was omitted in Comparative Example 3. The missing amount was made up by fluorosilicone modified polyurethane acrylate and acrylic polysiloxane in a weight ratio of 5:3. Other conditions were the same as in Example 1.
[0022] Comparative Example 4 Compared with Example 1, the only difference is that Comparative Example 4 uses an equal weight of silicone-fluorine modified alicyclic epoxy resin (Hubei Xinyuhong Biomedical Technology Co., Ltd., catalog number xyh001) instead of fluorosilicone modified polyurethane acrylate, while other conditions remain the same as in Example 1.
[0023] Comparative Example 5 Compared with Example 1, the only difference is that Comparative Example 5 uses an equal weight of methyl vinyl polysiloxane resin (Krmic, product name methyl vinyl MQ silicone resin) instead of acrylic polysiloxane, while other conditions remain the same as in Example 1.
[0024] Comparative Example 6 Compared with Example 1, the only difference is that Comparative Example 6 uses an equal weight of polydimethylsiloxane / acrylic copolymer (Hubei Langbowan Biomedical Co., Ltd.) instead of acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer, while other conditions remain the same as in Example 1.
[0025] Comparative Example 7 Compared with Comparative Example 1, the only difference is that the polymer resin of Comparative Example 7 was obtained by mixing fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer in a weight ratio of 2:5:3, while other conditions were the same as in Example 1.
[0026] Comparative Example 8 Compared with Comparative Example 1, the only difference is that the polymer resin of Comparative Example 8 was obtained by mixing fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer in a weight ratio of 3:2:5, while other conditions were the same as in Example 1.
[0027] Comparative Example 9 Compared with Comparative Example 1, the only difference is that in the preparation of the organic-inorganic abrasive in Comparative Example 9, an equal weight of γ-(methacryloyloxy)propyltrimethoxysilane (Chengfeng, CAS No. 2530-85-0) was used instead of γ-glycidoxypropyltrimethoxysilane, while the other conditions remained the same as in Example 1.
[0028] Comparative Example 10 Compared with Comparative Example 1, the only difference is that in the preparation of the organic-inorganic abrasive in Comparative Example 10, hexadecyltriethoxysilane (Chengfeng, CAS No. 16415-13-7) was used instead of dodecylmethyldiethoxysilane, while the other conditions were the same as in Example 1.
[0029] Comparative Example 11 Compared with Comparative Example 1, the only difference is that in the preparation of the organic-inorganic abrasive, dodecylmethyldimethoxysilane (Wuhan Kanos Technology Co., Ltd., product name: silane coupling agent KH-303) was used instead of dodecylmethyldiethoxysilane, while the other conditions remained the same as in Example 1.
[0030] Comparative Example 12 Compared with Comparative Example 1, the only difference is that in the preparation of the organic-inorganic abrasive in Comparative Example 12, γ-glycidoxypropyltrimethoxysilane was omitted and the missing amount was made up by an equal weight of dodecylmethyldiethoxysilane. All other conditions were the same as in Example 1.
[0031] Comparative Example 13 Compared with Comparative Example 1, the only difference is that in the preparation of the organic-inorganic abrasive in Comparative Example 13, dodecylmethyldiethoxysilane was omitted and the missing amount was made up by an equal weight of γ-glycidoxypropyltrimethoxysilane, while the other conditions were the same as in Example 1.
[0032] The frosted PET films prepared in Examples 1-3 and Comparative Examples 1-13 were used as samples. The samples were repeatedly rubbed with #0000 steel wool at a distance of 5 cm. The abrasion resistance of the frosted PET composite film was evaluated based on the number of abrasion marks on the sample surface under a 500g load, and the results are recorded in Table 1 below. The adhesion of the frosted layer on the sample surface was determined using the cross-cut test according to ASTM D3359, and the results are recorded in Table 1 below. The samples were characterized using a video optical contact angle meter (Dataphysics, Germany, OCA20 model) at 25°C with 5 μL of water droplets. The hydrophobicity of the samples was evaluated based on the water contact angle data. The average water contact angle data was taken after 5 measurements for each group of samples, and the results are recorded in Table 1 below. The samples were also characterized using a video optical contact angle meter (Dataphysics, Germany, OCA20 model) at 25°C with 3 μL of n-hexadecane. The antifouling properties of the samples were evaluated based on the oil contact angle data. The average oil contact angle data was taken after 5 measurements for each group of samples, and the results are recorded in Table 1 below.
[0033] Table 1 Abrasion resistance, 500g / use Adhesion / Grade Water contact angle / ° Oil contact angle / ° Example 1 34 0 123 80 Example 2 29 0 118 76 Example 3 32 0 121 78 Comparative Example 1 12 2 88 50 Comparative Example 2 15 3 92 54 Comparative Example 3 20 1 103 63 Comparative Example 4 14 3 91 52 Comparative Example 5 18 2 95 58 Comparative Example 6 21 1 105 65 Comparative Example 7 22 0 108 67 Comparative Example 8 20 1 112 71 Comparative Example 9 17 2 98 60 Comparative Example 10 24 1 112 72 Comparative Example 11 23 1 109 68 Comparative Example 12 15 3 107 66 Comparative Example 13 19 1 97 59 Based on the data in Table 1, compared with Example 1, Comparative Examples 1-3 respectively lacked the fluorosilicone-modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer in the polymer resin. Comparative Examples 4-6 respectively used polymer resins with similar effects to replace the three polymer resins in this invention. Comparative Examples 7 and 8 adjusted the weight ratio of the three components in the polymer resin. The final results showed a significant decrease in wear resistance, adhesion, water contact angle, and oil contact angle. This indicates that the three components in the polymer resin of this invention have special characteristics in terms of type selection and weight ratio, and the three work synergistically. Furthermore, when the fluorosilicone-modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate in the polymer resin are... When PET ester / polydimethylsiloxane methacrylate copolymer is mixed in a weight ratio of 4.5-5.5:2.5-3.5:1.5-2.5, the PET composite film exhibits better abrasion resistance, adhesion, water contact angle, and oil contact angle. In other words, the frosted PET composite film prepared in this manner demonstrates the best abrasion resistance, adhesion, water resistance, and stain resistance. Combined with the data from Example 1 and Comparative Examples 9-13, it is evident that this invention also possesses unique characteristics in the preparation of inorganic-organic abrasives. The micro-nano rough structure constructed by organic-inorganic abrasives with hydrophobic segments grafted onto the surface not only endows the composite film with superior abrasion resistance but also exhibits good compatibility with the polymer resin used in this invention. This results in the composite film displaying excellent adhesion, water contact angle, and oil contact angle, thereby achieving durable and highly efficient water and stain resistance.
[0034] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any indirect modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A frosted PET composite film, characterized in that, The frosted PET composite film includes a PET base film and a frosted layer. The raw materials of the frosted layer include polymer resin, organic-inorganic abrasives, leveling agents, photoinitiators, ultraviolet absorbers, defoamers, and diluents. The polymer resin is obtained by mixing fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer.
2. The frosted PET composite film according to claim 1, characterized in that, The weight ratio of the fluorosilicone modified polyurethane acrylate, acrylic polysiloxane, and acrylic (ester) / stearyl acrylate / polydimethylsiloxane methacrylate copolymer is 4.5-5.5:2.5-3.5:1.5-2.
5.
3. The frosted PET composite film according to claim 1, characterized in that, The weight ratio of the polymer resin, organic-organic abrasive, leveling agent, photoinitiator, ultraviolet absorber, defoamer, and diluent is 30-34:15-25:0.6-0.7:4.8-5.2:0.12-0.18:0.25-0.35:40-45.
4. The frosted PET composite film according to claim 1, characterized in that, The preparation of the organic-inorganic abrasive includes the following steps: A1. Mix nano-silica and N,N-dimethylformamide, disperse evenly, then add γ-glycidyl etheroxypropyltrimethoxysilane and dodecylmethyldiethoxysilane. Adjust the pH to 4-5 by adding acetic acid solution dropwise. Stir at 60-80℃ for 6-8 hours, centrifuge at 2000 rpm for 10 minutes, discard the supernatant, wash, and vacuum dry to obtain organic-inorganic abrasive.
5. The frosted PET composite film according to claim 4, characterized in that, The average particle size of the nano-silica in step A1 is 5-20 nm; the weight ratio of the nano-silica, N,N-dimethylformamide, γ-glycidyl etheroxypropyltrimethoxysilane, and dodecylmethyldiethoxysilane is 1:15-25:0.1-0.3:0.15-0.
4.
6. The method for preparing the frosted PET composite film according to any one of claims 1-5, characterized in that, Includes the following steps: B1. Mix the polymer resin, leveling agent, defoamer, and 1 / 2 of the diluent evenly. Add the organic-inorganic abrasive and pre-disperse at 800 rpm for 8-12 minutes. Then add the photoinitiator, ultraviolet absorber, and the remaining diluent and stir at 1000 rpm for 20-30 minutes to obtain the frosted functional layer coating. B2. The frosted functional layer coating is evenly applied to the surface of the PET film, dried under hot air at 60-80℃, and then placed in a UV curing oven for UV curing. After cooling to room temperature, the film is rolled up and cured at room temperature and 50% relative humidity for 24-28 hours to obtain the frosted PET composite film.
7. The preparation method according to claim 6, characterized in that, The coating amount described in step B2 is 8-20 g / m². 2 The UV curing radiation dose is 400-800 mJ / cm². 2 The time is 1-3 seconds.